2020
DOI: 10.1002/cssc.202000989
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Model Compounds of Lignin Linking Motifs; Synthesis and Selection Considerations for Reactivity Studies

Abstract: The development of fundamentally new valorization strategies for lignin plays a vital role in unlocking the true potential of lignocellulosic biomass as sustainable and economically compatible renewable carbon feedstock. In particular, new catalytic modification and depolymerization strategies are required. Progress in this field, past and future, relies for a large part on the application of synthetic model compounds that reduce the complexity of working with the lignin biopolymer. This aids the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 252 publications
(651 reference statements)
2
52
0
Order By: Relevance
“…However, the structure of lignin is more complex due to the presence of additional functionalities, and hence studies with more representative model compounds are desirable. Figure illustrates model compounds with increasing complexity that more closely mimic the most abundant β-O-4 linkage in lignin . Phenolic groups at the R 2 position in these model compounds represent β-O-4 linkages at the end of the lignin chain, while a methoxy group at R 2 position represents internal β-O-4 linkages.…”
Section: Introductionmentioning
confidence: 99%
“…However, the structure of lignin is more complex due to the presence of additional functionalities, and hence studies with more representative model compounds are desirable. Figure illustrates model compounds with increasing complexity that more closely mimic the most abundant β-O-4 linkage in lignin . Phenolic groups at the R 2 position in these model compounds represent β-O-4 linkages at the end of the lignin chain, while a methoxy group at R 2 position represents internal β-O-4 linkages.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of these linkage types depends on the lignin source, with β-O-4 type being the most abundant. 19 Consequently, also in our study, β-O-4 fragments and methoxy groups typical for lignin were introduced to the test reaction substrates. Furthermore, a lignin model monomer containing a 5-5' linkage was prepared and tested.…”
Section: Entry T (⁰C) Conversion 1[%] Yield 4[%] Yield 5[%] Yield 6[%]mentioning
confidence: 98%
“…Some of the key ways in which such phenylpropanoid residues are incorporated into the polymeric lignin framework are shown in Figure 13. A knowledge of these has informed studies of model compounds undertaken in efforts to define conditions for the controlled depolymerisation of lignins [48p,49] . So, for example, Hartwig and co‐workers have devised hydrogenolytic methods for the cleavage of biaryl ethers (see 73 ), and so affording the corresponding mixtures of aryls and phenols, [49b,d] while Ford et al have reported [49a] related means for cleaving dihydrobenzofurans (see 74 ).…”
Section: Ligninmentioning
confidence: 99%